Pengaruh Good Corporate Governance, Ukuran Perusahaan dan Leverage Terhadap Kinerja Keuangan Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) - Laisya Anindita Athifah; Fauzan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Financial performance reflects a company's ability to generate profits efficiently and sustainably. The mining sector is considered a high-risk industry that requires the optimal financial management. This study aims is to analyze the effect of Good Corporate Governance (GCG), firm size, and leverage on the financial performance of mining companies that listed on the Indonesia Stock Exchange during the 2020–2023 period. The research employs a quantitative approach with descriptive and verificative methods to describe the observed phenomena and test causal relationships between the variables. Secondary data were obtained from the annual reports of 24 mining companies and analyzed using multiple linear regression. The results show that Good Corporate Governance (GCG), that measured by institutional ownership, independent commissioners, and audit committees, has no significant effect on financial performance. In contrast, firm size and leverage have a significant positive effect, as indicated by a significance level of 0.000 for both variables.